2014
DOI: 10.1523/jneurosci.1779-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Receptor Patterning in a Higher Primate

Abstract: The mammalian olfactory system detects a plethora of environmental chemicals that are perceived as odors or stimulate instinctive behaviors. Studies using odorant receptor (OR) genes have provided insight into the molecular and organizational strategies underlying olfaction in mice. One important unanswered question, however, is whether these strategies are conserved in primates. To explore this question, we examined the macaque, a higher primate phylogenetically close to humans. Here we report that the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
73
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 54 publications
8
73
0
2
Order By: Relevance
“…Moreover, TMA-induced attraction required TAAR5 and PEA-induced aversion required TAAR4 (22,23). Together with the finding that individual fish and human TAARs recognize volatile amines aversive to those species (17,(24)(25)(26), these findings have suggested that the evolutionary conservation of the TAAR family may be linked to an ability to induce innate behaviors to volatile amines.…”
Section: Numerous Taar Ligands and Other Odorants Induce Innate Respomentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, TMA-induced attraction required TAAR5 and PEA-induced aversion required TAAR4 (22,23). Together with the finding that individual fish and human TAARs recognize volatile amines aversive to those species (17,(24)(25)(26), these findings have suggested that the evolutionary conservation of the TAAR family may be linked to an ability to induce innate behaviors to volatile amines.…”
Section: Numerous Taar Ligands and Other Odorants Induce Innate Respomentioning
confidence: 79%
“…Like ORs, TAARs are evolutionarily conserved in vertebrates (15)(16)(17), suggesting that TAARs may have a distinct function. Moreover, sensory neurons expressing TAARs appear to comprise a separate lineage (18)(19)(20), and genes encoding ORs and TAARs have different nuclear locations (20), which may contribute to TAARs' segregated expression in different neurons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although TAARs are only distantly related to biogenic amine receptors and they also have no phylogenetic relationship with classic chemosensory receptors, it appears that all subfamilies of TAARs, with the exception of TAAR1, serve chemosensory functions in detecting socially or ecologically relevant olfactory cues (Liberles and Buck, 2006;Hussain et al, 2009;Horowitz et al, 2014;Liberles, 2015). Indeed, mammalian TAAR2-TAAR9 subfamilies, as well as teleost-specific TAARs, have distinct expression patterns in the olfactory system, being present in the olfactory epithelium, and neonatal Grueneberg ganglion but not in the vomeronasal organ (Liberles and Buck, 2006;Fleischer et al, 2007;Hussain et al, 2009).…”
Section: E Trace Amine-associated Receptors In Olfactionmentioning
confidence: 99%
“…Ligands found thus far for TAARs are volatile amines, including several in mouse or predator urine (5,14,15). Ligands for a few mouse, fish, and human TAARs elicit aversive or attractive behaviors in their respective species, hinting at a conserved ability of TAARs to stimulate innate responses of potentially adaptive significance (5,6,14,16,17).…”
mentioning
confidence: 99%